Study and monitoring of Algerian crude oil desalting system by chemical analysis (Case study - Field of OURHOUD) - LOBZA Nour, Echourouk; BELOUL, Salah (Echahid Hama Lakhdar University of Eloued, 2023)
Desalination of crude oil is a key operation in the treatment process for reduce the salt and water content of the crude oil (the latter’s salinity is limited to 40 mg/L and BSW (Basic Sediment and Water) less than 1%) and for ensure the proper functioning of the various oil treatment facilities and avoid phenomena caused during treatment such as corrosion and clogging equipment.The purpose of this study is based on the verification of the desalination section to improved performance in quality with less cost. To this end, we have a technical study on the desalter (VW-21-01/02) followed by a verification calculation and we make the comparison between the obtained results and the designation then we conclude with an economic study.Keywords: desalination, electrostatic desalter, salinity, emulsion, coalescence ,Decantation, wash rate, demulsifier, electric field.تعد تحلية النفط الخام عملية رئيسية في عملية المعالجة لتقليل محتوى الملح والماء في النفط الخام )تقتصر ملوحة الأخير على 40 ملغم / لتر و BSW )الرواسب الأساسية والماء( أقل من 1٪( ولضمان حسن سير العمل في مرافق معالجة النفط المختلفة وتجنب الظواهر التي تحدث أثناء المعالجة مثل تآكل وانسداد المعدات. ويرتكز الغرض من هذه الدراسة على التحقق من قسم التحلية لتحسين الأداء من حيث الجودة وبتكلفة أقل. وتحقيقا لهذه الغاية، لدينا دراسة فنية عن التحلية ) 01/02 21 VW ) متبوعة بحساب التحقق ونجري المقارنة بين النتائج المتحصل عليها والتسمية ثم نختتم بدراسة اقتصادية.
مذكرة ماستر هندسة كيميائيةDes thèses génie chimique
Keywords: Keywords: desalination, electrostatic desalter, salinity, emulsion, coalescence ,Decantation, wash rate, demulsifier, electric field; الكلمات المفتاحية: تحلية المياه، تحلية الملوحة الكهروستاتيكية، الملوحة، المستحلب، الالتحام، التصفية، معدل الغسل، مزيل الاستحلاب، المجال الكهربائي.